Pro ASP.NET SharePoint 2010 Solutions Techniques for Building SharePoint Functionality into ASP.NET Applications - Milner, Dave.; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
You$1 (Bve run into this issue numerous times. You are developing an ASP.NET application, and you need to incorporate functionality that comes pre-packaged in SharePoint. Wikis, blogs, document management, user authentication, access management$1 (Bcommon needs across a variety of solutions. Without guidance and examples, interacting with underlying SharePoint components can be challenging, and working with the different SharePoint APIs is complicated. This book will introduce you to a variety of techniques to master the art of developing ASP.NET applications that are built upon a SharePoint foundation. With these techniques you can start using SharePoint as a development platform to enhance and complement your ASP.NET development. You$1 (Bll explore: Integration with SharePoint components The SharePoint/.NET/IIS implementation Configuration management Code Access Security Feature packaging Proper use of SharePoint APIs Advanced deployment techniques Pro ASP.NET Sharepoint 2010 walks you through all of the steps needed to successfully build and deploy ASP.NET solutions within the SharePoint platform. You'll then be able to greatly enhance your applications and build unique solutions that are a mixture of SharePoint and ASP.NET.s
Keywords: Computer science; Computer Science; Computer Science, general